Analysis of market dominance in the sharia banking industry after the merger of Bank Islamic Indonesia (BSI) - Airlangga Surya Kusuma; Faizi Faizi; Purwanto Widodo; Salma Asla Salsabila Praza; Muhammad Faturrohman Arkaan Sunyoto (Institute of Computer Science (IOCS), 2023)
To assist the development of the Islamic banking enterprise in Indonesia, the Government of Indonesia through the Ministry of BUMN decided to merge 3 BUS which can be subsidiaries of BUMN Banks, namely Bank Syariah Mandiri, BNI Syariah and BRI Syariah. The merger ended in a bank with the call Bank Syariah Indonesia (BSI) and officially running on February 1, 2021. At the give up of 2021, BSI was recorded as having assets of IDR 265.3 trillion and changed into included inside the top 10 largest national banks in Indonesia. Islamic banks have to this point had confined capital, making it tough to compete with traditional banks. Therefore, BSI, which has massive capital, is anticipated for you to compete head to head with conventional banks. There have been also concerns and rejection of the BSI merger. This is due to the fact there are indicators that BSI has market dominance and might monopolize the Islamic banking industry in Indonesia. The motive of this examine is to describe the characteristics of marketplace dominance within the Islamic banking enterprise after the merger of Bank Syariah Indonesia. This research uses some of indicators, particularly awareness ratio, Herfindahl–Hirschman Index (HHI), and Melnik's ratio. The end of this look at is that of all of the indicators used, namely the awareness ratio, Herfindahl–Hirschman Index (HHI), and the Melnik ratio, it can be stated that there is a robust indication of marketplace dominance inside the Islamic banking industry after the merger of Bank Syariah Indonesia